PENGEMBANGAN E-MODUL ETNOPEDAGOGI BERBASIS NILAI DALIHAN NA TOLU UNTUK MENINGKATKAN LITERASI KRITIS DAN TANGGUNG JAWAB MAHASISWA - Martua Siregar; Fitri Romaito Lubis; Yulia Rizki Ramadhani (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2026)
Objective: This study aims to develop and examine the effectiveness of an ethnopedagogical e-module based on Dalihan Na Tolu values in enhancing students’ critical literacy and responsibility in higher education. The integration of local wisdom into digital learning is expected to improve learning relevance and strengthen character development. Methods: This study employed a Research and Development (R&D) approach using the ADDIE model, including analysis, design, development, implementation, and evaluation stages. The subjects were ten students of the Public Administration Study Program at Universitas Graha Nusantara selected through purposive sampling. Data were collected through observation, interviews, documentation, and pre-test and post-test. Results: Expert validation indicated that the e-module was valid with an average feasibility score of 85%. The results showed an increase in students’ critical literacy from 54.3 (pre-test) to 73.0 (post-test), while responsibility improved from 2.7 to 4.2. The paired sample t-test revealed that the improvement was statistically significant (p < 0.05). Novelty: This study contributes an innovative ethnopedagogical e-module integrating Dalihan Na Tolu values with digital learning to foster critical literacy and student responsibility.